Ultrasonographic findings in the ovine udder during involution. Issue 3 (August 2014) - Petridis, Ioannis G; Gouletsou, Pagona G; Barbagianni, Marianna S; Amiridis, George S; Brozos, Christos; Valasi, Irene; Fthenakis, George C
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of the study was to record, by means of ultrasonographic examination, changes occurring in the udder of ewes during involution and to compare differences between progressive or abrupt udder drying-off. In group A ewes, udder drying-off took place progressively during a period of 22 d; ewes were milked twice daily for the last time on day(D) 0; then, they were hand-milked once daily for a week (D1–D7), which was followed by another week during which ewes were hand-milked once every 2 d (D9, D11, D13), followed by a third week during which ewes were hand-milked once every 3 d (D16, D19, D22). In group B ewes, the procedure took place abruptly; ewes were milked twice daily for the last time on D0 and no milking was carried out after that. B-mode and Doppler ultrasonographic examination of the udder of all ewes was performed throughout the drying-off procedure. Appropriate data management and analysis were performed. Progressive changes of the various parameters evaluated throughout the study period were significant in both groups (P<0·005). Gray-scale results of mammary parenchyma progressively decreased during the study and differed significantly between group A and group B (P=0·049). A temporary increase in cistern volume was evident after cessation of lactation, but differences were not significant between the two groups (P>0·3). Diameter of the external pudendal artery progressively decreased during the study and differed significantly between the two groups (P=0·037). Both resistance index and pulsatility index progressively increased throughout the study period in both groups; for both parameters, differences between the two groups were significant (P<0·0005). B-mode ultrasonographic examination indicated differences in remodelling of the extracellular matrix in relation to the procedure for udder drying-off. Volume of the gland cistern did not appear to be affected by the procedure for udder drying-off. Doppler ultrasonographic examination confirmed that blood flow during initiated involution was lower than during a progressive procedure for drying-off.